Identificando Locais Influentes Através de Palavras-Chave - Silva, Felipe Pains Oliveira (2019)
Spatial data or spatial objects are used by various applications such as Google Maps or Uber. These applications provide location services for users, such as: finding the nearest restaurant or driver. Similarly, the influential location query aims to find the best place for the installation of a new establishment, according to the weight of the objects in its vicinity. Weight is a constant predefined by applications, such as the number of stars or the number of people in a house. In this research, we study a new type of query where the weight of objects are defined taking into account a set of keywords defined by the user. Therefore, it is possible to select relevant neighbors based on user preference. In this research a new type of query is specified, new algorithms are presented to process this query efficiently and the algorithms proposed in real data sets have been evaluated.